Supernormal Electro-Oculograms in Patients with Neurofibromatosis Type 1 - Lubiński Wojciech (Hereditary Cancer in Clinical Practice, 2004)
Abstract Purpose To asses the retinal pigment epithelium (RPE) function measured by EOG testing in patients with neurofibromatosis type 1 (NF-1). Our preliminary EOG results suggested dysfunction of the RPE in individuals with NF-1. In order to confirm our initial results we performed EOG examination on a larger group of NF-1 patients. Patients Studies were performed on 36 patients with clinically diagnosed NF-1 and compared to normal healthy controls. Methods Standard EOG recordings were performed in accordance with the International Society for Clinical Electrophysiology of Vision (ISCEV) standards. Results In NF-1 patients the Arden indexes of the EOG test were significantly higher primarily due to the lower values of dark troughs. Supernormal EOGs (exceeding the value of the mean + 2 SD from the control group) were present in 58% of NF-1 patients. Conclusions Dysfunction of the RPE is a characteristic feature of individuals with NF-1.